Association of Age, Parity and Body mass Index with Hemoglobin and Serum Ferritin Levels in Pregnant Women in Baghdad City - Moustafa, Mayada M.; kasim, Ali Abdulhussain; Al-Janabi, Rawaa Dawood (Iraqi Journal of Pharmaceutical Sciences, 2021)
Hemogloin (Hb) and serum ferritin levels are used to assess anemia in pregnancy. Some studies referred to the influence of maternal age, body mass index (BMI) and parity on Hb and serum ferritin levels. The study aimed to examine the possible association of maternal Hb and serum ferritin with maternal age, parity, and BMI in a sample of pregnant women in Baghdad. Ninety healthy pregnant women, grouped in three equal groups according to the pregnancy trimester, and thirty apparently healthy non-pregnant women from Baghdad were enrolled in this observational study. Blood and serum samples were obtained for the estimation of Hb and serum ferritin levels.The pooled data of participants showed a negative correlation between parity and each of blood Hb concentrations (r= -0.147, P=0.046) and plasma ferritin levels (r= -0.186, P= 0.038). The negative correlation of parity with blood Hb concentration was reported in participants in the third trimester of pregnancy (r= -0.270, P=0.048); and between parity and plasma ferritin levels in the second (r= -0.088, P= 0.046) and third (r= -0.398, P=0.029) trimester pregnant. The study did not report a significant correlation between age and BMI with blood Hb concentrations or serum ferritin levels in pregnant women at any trimester of pregnancy.There is a negative correlation between parity and each of blood Hb concentration and serum ferritin levels in pregnant women in Baghdad. While, there is no such correlation with maternal age and BMI at any trimester of pregnancy.